2017
DOI: 10.1152/ajprenal.00231.2016
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of mPGES-1 exacerbates renal fibrosis and inflammation in mice with unilateral ureteral obstruction

Abstract: Microsomal prostaglandin E synthase-1 (mPGES-1), an inducible enzyme that converts prostaglandin H to prostaglandin E (PGE), plays an important role in a variety of inflammatory diseases. We investigated the contribution of mPGES-1 to renal fibrosis and inflammation in unilateral ureteral obstruction (UUO) for 7 days using wild-type (WT) and mPGES-1 knockout (KO) mice. UUO induced increased mRNA and protein expression of mPGES-1 and cyclooxygenase-2 in WT mice. UUO was associated with increased renal PGE conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
(58 reference statements)
2
15
0
Order By: Relevance
“…cAY is a very potent EP4 agonist and is highly selective of EP4 over EP1-3 or other prostanoid receptors (35). Studies have indicated that cAY effectively activates endogenous EP4 signaling by increasing cAMP production in various animal and human tissues (36)(37)(38)(39)(40). In the present study, cAY protected the liver from I/R in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 56%
“…cAY is a very potent EP4 agonist and is highly selective of EP4 over EP1-3 or other prostanoid receptors (35). Studies have indicated that cAY effectively activates endogenous EP4 signaling by increasing cAMP production in various animal and human tissues (36)(37)(38)(39)(40). In the present study, cAY protected the liver from I/R in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 56%
“…Our present study found that mPGES-1 is activated in the peritoneum of PD patients with UFF, and the expression was also increased in RPMCs treated with high glucose. The results from this study revealed that, in addition to the acute phase of diseases, mPGES-1 is still activated under sustained pathological stimulation, a finding that was consistent with the induction of mPGES-1 in peripheral blood mononuclear cells from hypertensive patients, kidney tissues of the unilateral ureteral obstruction mouse model and renal proximal tubular cells treated with albumin (27)(28)(29). Additionally, in our study, a positive correlation was found between the expression of mPGES-1 in the peritoneum and degree of peritoneal fibrosis.…”
Section: Discussionsupporting
confidence: 83%
“…However, the role of mPGES-1 in fibrosis is controversial according to previous studies. In the unilateral ureteral obstruction mouse model, mPGES-1 exerts a potentially protective effect against renal fibrosis, while inhibition of mPGES-1 provides a viable method to alleviate the development of bleomycin-induced skin fibrogenesis ( 27 , 30 ). These different effects on fibrosis may be attributed to different models of disease and tissue-specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The aggravation of AKI by downregulating mPGES-2was demonstrated to be associated with autophagy inhibition and enhanced apoptosis [ 57 ]. Multiple researches uncovered a remarkable role of mPGES-1 deletion on PGE2 production in various models including endotoxemia- and cisplatin-induced kidney injury [ 58 ], lithium-induced NDI [ 59 ], Ang II- and DOCA-salt-induced hypertension [ 60 ], aldosterone escape [ 61 ], and unilateral ureteral obstruction [ 62 ]. Different from these observations, in the diabetic kidney disease model induced by STZ, three forms of PGES were unaltered in the kidney, and deletion of mPGES-1 did not suppress renal PGE2 production [ 63 ].…”
Section: Pge2 In Kidney Diseasesmentioning
confidence: 99%
“…In kidney cells, we also found that mPGES-1-derived PGE2 could activate Stat3 signaling to promote podocyte apoptosis [ 66 ], and the proliferation of mesangial cells triggered by uric acid and uremic toxin indoxyl sulfate was attenuated by silencing mPGES-1 [ 67 , 68 ]. However, in a UUO model, mPGES-1 was shown to exert a protective effect against renal fibrosis and inflammation [ 62 ]. Moreover, in the type-1 diabetic model induced by STZ, both renal PGE2 production and glomerular injury were unaffected in mPGES-1 KO mice.…”
Section: Pge2 In Kidney Diseasesmentioning
confidence: 99%